La propiedad industrial en Venezuela: desarrollo institucional y experiencia normativa (1955-2017) - Troconis Troconis, Aura Esther (2018)
Intangible assets represent challenges and opportunities for the countries, thatare translated into creations in favor of their economic and social development. The protection of this heritage is the responsibility of the States along with the actors that make up the National Science, Technology and Innovation Systems (Sistemas Nacionales de Ciencia, Tecnología e Innovación -SNCTI), through the generation of public policies and legislations in harmony with national expectations, trade and international relations.The objective of this article is to present an institutional and normative journey of the development of industrial property in Venezuela, through the vision of the entities, the legislations and public policies developed in the country from 1955 to 2017.The methodology used in the research is mainly theoretical and documentary. In that sense, this research is descriptive and analytical, therefore was structured on the basis of the revision of various national and international sources of specialized organizations, bibliographical and newspaper, among which are, reports, minutes, laws, agreements, decisions, projects and plans generated that reflect both the background and the current situation of such processes